Development of Quick Reference Manual for the Management of Drug Overdose and Poisoning - Alan Tom1 , Mohammed Salih1 , N Venkateswaramurthy1 , R Sambathkumar1 (Indian Journal of Forensic Medicine & Toxicology, 2021)
Aim: To develop a reference manual for the management of drug overdose and poisoning.Methods: A prospective developmental study was performed for a span of six months at a tertiary carehospital in Erode. Information on the management of cases of drug overdose and poisoning was providedbased on queries received at the Drug Information Center and the poisoning cases identified in the respectivehospital over the past three years. Further attention was paid to detecting local poisons. Such informationwas collected on the basis of literature reviews, magazines and newspapers. In addition to drug and poisonmonographs; android applications, toxicological databases and links, standard reference books and articleson drug overdose and poisoning were included. Locally reported cases have been given more focus.Results: A formulary was prepared which includes the management information for 100 drugs and 57 toxicsubstances that were identified after extensive research. The signs and symptoms of the various poisoningcases were graded as mild, moderate and severe based on poison severity scale (PSS) and respective antidoteswere mentioned.Conclusion: As per our knowledge, this is the first formulary that focus on local poisons. The implementationof the formulary may have a significant impact on healthcare professionals to improve the quality of lifeof patients.This provides important information of localized poisoning and drug overdose in a nutshell andtherefore offers as a quick data to the enquirer.